Multicomponent Intervention to Reduce Gaps in the Hypertension Care and Control Process - Addys María Díaz Piñera; Tullia Battaglioli; Armando Rodríguez Salvá; Esteban Londoño Agudelo; Lisvett González Rodríguez; Patrick Van der Stuyft (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Background: the evidence on Public Health interventions to improve deficiencies in the care and control of hypertensive people continues to be insufficient. Objective: to implement a multicomponent intervention to reduce these gaps in the Julio Antonio Mella Polyclinic in the Guanabacoa municipality, to evaluate the intervention process, its effectiveness and the fidelity of its implementation. Method: in relation to the results obtained in the baseline study, national and international technical recommendations, a multicomponent intervention was designed that will have the following components: reorganization of health services, training of health personnel, empowerment of patients and community participation. The effectiveness of the intervention will be evaluated through a quasi-experimental study (before and after). The intervention will cover the aforementioned polyclinic, the ten baseline study clinics, and the population served by them. Two years after the start of implementation, a population survey will be applied again and the difference in the magnitude of the pre-post intervention population gaps will be estimated. In addition, the process will be monitored and the fidelity of the implementation of the intervention will be evaluated. Results: reduce existing gaps in the process of care for hypertensive patients, identify their magnitude in relation to the baseline. Conclusions: the study will provide evidence to the Cuban Ministry of Public Health and other countries, especially in Latin America, to improve the care of chronic patients.